An investigation into using situational contexts in teaching grammar for non-English major freshmen in a university in Nam Dinh city - Lại, Thị Hiền (ĐHNN, 2017)
In order to be fluency in English, grammar is considered to be the basis to develop other four skills. However, when teaching grammar to first - year students at University of Economics and Technical Industry, the author of this research found out that students were not interested in learning grammar. Hence, they did not focus on the lesson and ignored doing exercises resulting in bad marks in the tests and exams. Thanks to the reasons above, the researcher decided to use situational contexts to teach grammar for students. The aims of carrying out this research were to find out students‟ interest in grammar lessons which apply situational contexts and measure whether students can complete grammar exercises better after practicing with situational contexts. In order to do this research, the researcher first makes plans for the study by preparing situational contexts and deciding how they are applied in the classroom. Then, the action stage takes place. All the situational contexts are put into practice. The teacher gives them to students and they have to make presentation about those situational contexts.